STUDY OF THE APPLICATION OF JAVANESE ORNAMENTS TO INDONESIA RAILWAY STATION (CASE STUDY OF TAWANG SEMARANG STATION, SEMARANG PONCOL STATION, YOGYAKARTA STATION) - Masruroh, Evita Luthfi; Winarto, Erwin Djuni (Border: Jurnal Arsitektur, 2022)
Station is a facility and infrastructure used to support train passengers. Development in the station area is expected to be a solution and can optimize the added value of management and can be an alternative to public transportation. Each region has its own characteristics and characteristics. Java is an area that still holds customs and culture. Javanese buildings are synonymous with ethical values and aesthetic values. Variety of Javanese building ornaments in the form of ornaments that have a philosophy as a clue to the level of degrees. But now the value of Javanese culture began to fade along with the times. The application of Javanese architectural ornaments to station buildings in Indonesia is one form of way to maintain and introduce the local culture of an area through building facilities. This research aims to examine the application of Javanese Architectural ornaments to railway station buildings in Indonesia. The method used is qualitative descriptive using a qualitative rationalistic analysis approach. With secondary data collection techniques and utilizing library study data, media analysis, and observation. The results showed that many train stations still use heritage architecture, however, elements of Javanese langgam in the form of ornaments appeared in buildings which are a form of cultural acculturation between countries.